PENGARUH HARDSKILL DAN SOFTSKILL TERHADAP KEMAMPUAN MERANCANG PROSPEK USAHA MELALUI KEPERCAYAAN DIRI PADA MAHASISWA DAN ALUMNI STIE AMM MATARAM - Anna Apriana Hidayanti; Baiq Desthania Prathama (Sekolah Tinggi Ilmu Ekonomi AMM, 2019)
This study aims to determine the effect of hardskill, softskill and confidence in the ability to design business prospects. The method used in this research is Path Analysis, which is used in testing the amount of contribution (contribution) that is addressed by the path coefficients in each path diagram of direct or indirect causal relationships between hardskill variables and softskill towards designing business prospects through confidence variable. Data collection tools are carried out by distributing questionnaires to students who have taken entrepreneurship courses in theory and practice and alumni of the 2015-2016 class taken by strata random sampling techniques and then tabulated using a Likert scale to determine the influence of the formation of the mindset of students and alumni in designing business prospects that are influenced by hard skills, softskill and confidence. The results of the research showed that the hardskill and softskill variables had a significant effect on the ability to design business prospects of STIE AMM students and alumni while the confidence variable had no significant effect on the ability to design business prospects of STIE AMM Mataram students and alumni. The direct effect of hardness variable (X1) on self confidence (Z) is 0.234 and the direct effect of softskill variable (X2) on self confidence (Z) is 0.294. The direct effect of hardskill variable (X1) on the ability to design business prospects (Y) is 0.201. The direct influence of softskill variable (X2) on the ability to design business prospects (Y) is 0.369. The direct effect of confidence (Z) on the ability to design business prospects (Y) is 0.077. The indirect effect of hardskill variable (X1) on the ability variable to design business prospects is 0.018018 and the indirect effect of softskill variable (X2) on the ability variable to designate business prospects is 0.022869